Agenda responsiveness in the European Council: public priorities, policy problems and political attention. Issue 4 (3rd July 2016) - Alexandrova, Petya; Rasmussen, Anne; Toshkov, Dimiter
Abstract: The existence of political responsiveness in multi-level systems like the EU remains an open question despite significant recent research on the topic. This article studies whether the European Council responds to the shifting policy priorities of European citizens. More specifically, it explores the synchronic and diachronic associations between what people consider to be the most important problems and the political attention devoted to these issues from 2003 to 2014. The economic crisis after 2008 appears to have made the ranking of public concerns and the European Council agenda more alike. However, a detailed examination of the shifts in prioritisation of single issues over time reveals little evidence for dynamic issue responsiveness. Recently the European Council has paid more attention to the issues that the public considered the most pressing problems but the convergence could possibly be driven by the intensity of the underlying policy problems.